(untitled) (Philosophy and Progress, 2022)
Karl Raimund Popper, (1902-1994) a leading apostle of antiinductivism, holds that the main problem of philosophy of science is the problem of demarcation. Accordingly, the demarcation principle distinguishes science from non-science. To Popper, logic, metaphysics and psychoanalysis are likely to fall into the non-science group. Principle of induction has been accepted even though resentfully as the chief tool of scientific investigation by the positivists as well as the scientists in general. Popper rejects the positivistic approach and on the contrary proposes falsifiablity to furnish his iconoclastic project. This paper intends to indentify the problem of his very approaches in order to hold that in spite of some difficulties in the problem of induction itself, as the identifier of science, we do not have any alternative to save science from metaphysics. Finally, Popper’s so-called demarcation criterion is extensively examined here with a view to defend material aspect of inductive generalization. Philosophy and Progress, Vol#67-68; No#1-2; Jan-Dec 2020 P 33-48